Biocatalytic Reduction of HMF to 2, 5‐Bis(hydroxymethyl)furan by HMF‐Tolerant Whole Cells. Issue 2 (14th December 2016) - Li, Yan‐Mei; Zhang, Xue‐Ying; Li, Ning; Xu, Pei; Lou, Wen‐Yong; Zong, Min‐Hua
Abstract: Catalytic upgrading of 5‐hydroxymethylfurfural (HMF), an important biobased platform chemical for high‐value products, is currently of great interest. In this work, a new highly HMFtolerant yeast strain— Meyerozyma guilliermondii SC1103 was isolated, and biocatalytic reduction of HMF to 2, 5‐bis(hydroxymethyl)furan (BHMF) using its resting cells was reported. Cosubstrates exerted a significant effect on the catalytic activity and selectivity of microbial cells as well as their HMF‐tolerant levels whereas the nitrogen source and mineral salts had no effects. In addition, M. guilliermondii SC1103 cells exhibited good catalytic performances within the range of pH 4.0–10.0. The yeast was highly tolerant to both HMF (up to 110 mm ) and BHMF (up to 200 mm ). In addition, 100 mm HMF could be selectively reduced to BHMF within 12 h by its resting cells in the presence of 100 mm glucose (as cosubstrate), with a yield of 86 % and selectivity of >99 %. The production of 191 mm of BHMF was realized within 24.5 h by using a fed‐batch strategy, with a productivity of approximately 24 g L −1 per day. In addition, this new biocatalytic approach was applied for the reduction of furfural and 5‐methylfurfural, affording the corresponding furfuryl alcohols with yields of 83 and 89 %, respectively. Abstract : High HMF tolerance and selectivity ! An efficient and selective biocatalytic approach for the synthesis of 2, 5‐bis (hydroxymethyl)furan (BHMF) from 5‐hydroxymethylfurfural (HMF) is successfully developed by using highly HMF‐tolerant Meyerozyma guilliermondii SC1103 cells for the first time. A fed‐bath strategy was used for the synthesis of BHMF, obtaining a good yield and excellent selectivity.